The Effect of the Adiwiyata Program on Students' Environmental Awareness - Dina Nur Istikomah; Nirva Diana; Yetri Hasan (ETDC: Indonesian Journal of Research and Educational Review, 2026)
The Adiwiyata program at Junior High School 1 Adiluwih has been running with adequate support and has succeeded in forming an evenly distributed environmental awareness among students. This study aims to examine and analyze the effect of the implementation of the Adiwiyata program on students' environmental awareness at Junior High School 1 Adiluwih, Pringsewu Regency. This study used a quantitative approach with a correlational design on a sample of 194 students in grades VIII and IX. Data were collected through questionnaires and analyzed using simple linear regression techniques. The results showed that the implementation of the Adiwiyata program and the level of students' environmental awareness were in the "fairly good" category with a homogeneous data distribution. Statistical analysis confirmed a positive and significant effect of the Adiwiyata program on students' environmental awareness (p < 0.001) with a regression equation of Y = 9.756 + 0.694X. The coefficient of determination of 0.600 indicates that the Adiwiyata program provides a dominant contribution of 60% in forming students' environmental awareness. These findings provide empirical evidence that the quality of the Adiwiyata program implementation is a key factor in increasing ecological awareness and strengthening sustainable school culture practices.